Pronomina Persona dalam Bahasa Modole: Kajian Morfosintaksis - sadiyah, Umiatun Sadiyah; Mastoyo, Yohanes Tri (Kajian Linguistik dan Sastra, 2025)
The Modole language, abbreviated (BM), is part of the West Papua language phylum spoken by theModole Tribe in Kao District, North Halmahera Regency, North Maluku Province. This study aims todescribe the form and characteristics of personal pronouns in BM. In addition, this study is a form ofdocumentation as an effort to preserve, protect, and develop BM. This study is descriptive qualitativewith a morphosyntactic approach. The data in this study are direct speech in the form of words, phrases,clauses, and sentences using morphological questionnaires and syntactic questionnaires. The datacollection method uses the listening method with the note and record technique, and the conversationmethod with the fishing technique. The data analysis method of this study uses the name and namingmodel analysis method to analyze the form of pronouns in BM, which has a major influence on changesin the form of verbs, including the process of the emergence of proclitics in the verbs. The results of thestudy indicate that the second singular personal pronoun in BM recognizes gender differences, and theform of the BM personal pronoun can change the verb construction by producing proclitics in the verbs.In addition, verb constructions are found in all forms of BM pronouns.